2019
DOI: 10.1172/jci124608
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial barrier repair and prevention of allergy

Abstract: Allergic diseases such as atopic dermatitis (AD), food allergy (FA), asthma, and allergic rhinitis affect more than 30% of the population (1-3). These diseases have in common a dysfunctional epithelial barrier, resulting in the penetration of allergens and microbes, accompanied by the release of epithelial-derived cytokines (e.g., thymic stromal lymphopoietin [TSLP], IL-25, IL-33), which drive type 2 immune responses. Although other immune pathways can modify the course of illness, cytokines including IL-4, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
182
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(187 citation statements)
references
References 215 publications
(276 reference statements)
2
182
0
3
Order By: Relevance
“…Consequently, epithelial dysregulation and mutations or polymorphisms of genes important for skin barrier, such as filaggrin, SPINK5, 1 and SERPINB7, have been linked to eczema development and also food allergy. [2][3][4][5][6] Recently, electrical impedance spectroscopy has shown promising results in rodents to measure skin barrier function. This is of relevance since it can be easily adapted for usage on humans.…”
Section: Food Allergy and Barrier Functionmentioning
confidence: 99%
“…Consequently, epithelial dysregulation and mutations or polymorphisms of genes important for skin barrier, such as filaggrin, SPINK5, 1 and SERPINB7, have been linked to eczema development and also food allergy. [2][3][4][5][6] Recently, electrical impedance spectroscopy has shown promising results in rodents to measure skin barrier function. This is of relevance since it can be easily adapted for usage on humans.…”
Section: Food Allergy and Barrier Functionmentioning
confidence: 99%
“…The skin barrier prevents excessive water loss, as well as the entry of microorganisms, allergens, and chemical substances. Dysfunction of the skin barrier causes infectious diseases and skin disorders such as atopic dermatitis and ichthyosis (1)(2)(3). Skin consists of the epidermis, dermis, and subcutaneous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic asthma continuously display chronic inflammation and oxidative stress [8]. Furthermore, pulmonary epithelial cells and immune cells are continuously activated, and they release various inflammatory cytokines, inflammatory mediators, and oxidative molecules that damage cells and tissues, which reduces lung function [6,29]. Previous studies have shown that some natural products could reduce airway inflammation in asthmatic mice [30,31].…”
Section: Discussionmentioning
confidence: 99%